Graphene quantum dots promote migration and differentiation of periodontal ligament stem cells - Liang, Yan; Gao, Wanshan; Deng, Sicheng; Wu, Dongyan; Jiang, Yiling; Zhang, Yishan; Qiu, Rongmin (Frontiers in Chemistry, 2023)
Graphene and its derivatives have attracted much attention as nanomaterials in bone tissue engineering because of their remarkable ability to induce cell osteogenic differentiation. However, graphene quantum dots (GQDs), as graphene derivatives, little is known about their osteodifferentiation- and osteoinduction-promoting capabilities, especially in the restoration of bone defect caused by periodontitis. Therefore, there is a growing need to investigate the effect of GQDs on periodontal ligament stem cells (PDLSCs). Here, we postulated that GQDs are a promising biocompatible nanomaterial that facilitated the migration and differentiation of PDLSCs, and use laboratory methods like CCK-8, transwell experiments, qRT-PCR, Alizarin red staining and immunofluorescence staining to evaluate. Our experiments confirmed that GQDs did not inhibit cell viability, with most cells remaining viable even at GQDs concentrations of up to 30 μg mL-1. Moreover, GQDs were found to significantly enhance PDLSC migration, with the peak effect observed at concentrations of 5 and 10 μg mL-1. Furthermore, GQDs accelerated osteoblastic differentiation in PDLSCs and induced the mineralization of calcium nodules. Additionally, GQDs were shown to promote fibroblast differentiation in PDLSCs compared to the control group. Thus, GQDs not only possessed low cytotoxicity and good biocompatibility, but also displayed the beneficial capability to migration and differentiation of PDLSCs, which indicated GQDs might be a potential nanomaterial for bone regeneration.